Identification of Antioxidant Activity of Bridelia Micrantha Bark Using the DPPH Method - Bayani, Faizul; Rosmayanti, Baiq; Hamdani, Ade Sukma; Bimaharyanto, Deden Eka; Hulyadi, Hulyadi (Hydrogen: Jurnal Kependidikan Kimia, 2024)
This research aims to identify the antioxidant activity of Bridelia micrantha stem bark using the DPPH method. This research is a laboratory experimental research. Antioxidant activity was measured using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Melandean Bark Extract is made using the maceration method with 80% methanol solvent. Identification of antioxidant activity was carried out at concentrations of 20 ppm, 40ppm, 60ppm, 80ppm, and 100ppm. Vitamin C was used as a positive control. Absorbance measurements were carried out using a UV-Vis spectrophotometer at a wavelength of 517nm. The test results in this research showed that the IC50 value of melandean bark extract was 85.54 ppm. Melandean bark extract is classified as a strong antioxidant.